(Dys)regulation of Synaptic Activity and Neurotransmitter Release by β-Amyloid: A Look Beyond Alzheimer's Disease Pathogenesis - Fagiani, Francesca; Lanni, Cristina; Racchi, Marco; Govoni, Stefano (Frontiers in Molecular Neuroscience, 2021)
Beside its widely studied role in the pathogenesis of Alzheimer’s Disease (AD), β-amyloid (Aβ) is a normal and soluble product of neuronal metabolism that regulates several key physiological functions, exerting neuromodulatory effects on synaptic plasticity, memory, and neurotransmitter release. Such effects have been observed to occur in a hormetic fashion, with Aβ exhibiting a dual role influenced by its concentration, the different isoforms or aggregation forms of the peptide. However, to date, our knowledge about the physiological functions of A and, in particular, its modulatory role on synaptic activity and neurotransmission in the normal brain is fragmentary, thus hindering a clear comprehension of the biological mechanisms underlying the derangement from function to dysfunction. In particular, according to the amyloid cascade hypothesis, the switch from physiology to pathology is linked to the abnormal increase in Aβ levels, due to an imbalance in Aβ production and clearance. In this regard, increased Aβ levels have been hypothesized to induce early defects in synaptic function and such alterations have been suggested to account, at least in part, for the onset of neuropsychiatric symptoms (e.g. apathy, anxiety, changes in mood, depression, agitation/aggression), frequently observed in the prodromal stage of AD. Therefore, understanding the biological mechanisms underlying early synaptic alterations in AD is a key starting point to frame the relevant time windows for AD treatment and to gain insight into AD etiopathogenesis.